Investigation of irradiated graphene oxide/ultra-high-molecular-weight polyethylene nanocomposites by ESR and FTIR spectroscopy. Issue 11 (1st November 2016) - Huang, Guodong; Ni, Zifeng; Chen, Guomei; Li, Guangfei; Zhao, Yongwu
ABSTRACT: Graphene oxide/ultra-high-molecular-weight polyethylene (GO/UHMWPE) nanocomposite has a potential application for artificial joints. However, free radicals and antioxidative properties of irradiated GO/UHMWPE were not clearly clarified. In this paper, GO/UHMWPE nanocomposites were prepared and irradiated by gamma-irradiation with a dose of 100 kGy. Afterward, test samples were aged in air. Free radicals and molecular structures of test samples were investigated by electron spin resonance (ESR) spectroscopy and Fourier transform infrared (FTIR) spectroscopy, respectively. These studies indicated that irradiation enhanced GO radical concentrations. And GO radicals were stable in air and even could not be quenched after accelerated aging. GO radicals were superimposed on free radicals of irradiated UHMWPE. Although GO showed free radical-scavenging capacity, the influence of GO on free radicals of irradiated UHMWPE was too weak to be observed in ESR spectroscopy. Free radicals concentrations of irradiated GO/UHMWPE nanocomposites were gradually decayed with aging time evolving in air. Observing the oxidation index values of test samples, it was proposed that irradiated GO/UHMWPE might show very weak antioxidative properties.